2020
DOI: 10.1101/2020.04.02.020081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monocyte-derived Prostaglandin E2 inhibits antigen-specific cutaneous immunity during ageing

Abstract: Ageing results in a decline in immune function. We showed previously that healthy older humans (>65 years old) have reduced antigen-specific cutaneous immunity to varicella zoster virus (VZV) antigen challenge. This was associated with p38 MAP kinase driven inflammation that was induced by mild tissue injury caused by the injection of the antigen itself. Here we show that non-specific injury induced by injection of air or saline into the skin of older adults recruits CCR2+CD14+ monocytes by CCL2 produced by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…Previous papers that have discussed COVID-19 in the context of aging and immunesenescence have speculated that inflammaging would predispose the older adult to severe infection by fuelling an exaggerated pro-inflammatory response to SARS-CoV-2 ( 202 , 203 ). However, based on emerging data that suggests excessive pro-inflammatory responses in older adults negatively regulates their immune responses ( 204 , 205 ), we propose the following alternative hypothesis: inflammaging predisposes older adults to severe COVID-19 by suppressing the immune response to SARS-CoV-2 . Whilst in vitro and in vivo studies have demonstrated that exposure to pro-inflammatory cytokines can modulate the phenotype and/or function of innate and adaptive immune cells ( 147 149 , 206 ), it is the work of Akbar et al that have specifically linked hyper-inflammation to impaired antigen specific immune responses during aging.…”
Section: Pathogen Eliminationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous papers that have discussed COVID-19 in the context of aging and immunesenescence have speculated that inflammaging would predispose the older adult to severe infection by fuelling an exaggerated pro-inflammatory response to SARS-CoV-2 ( 202 , 203 ). However, based on emerging data that suggests excessive pro-inflammatory responses in older adults negatively regulates their immune responses ( 204 , 205 ), we propose the following alternative hypothesis: inflammaging predisposes older adults to severe COVID-19 by suppressing the immune response to SARS-CoV-2 . Whilst in vitro and in vivo studies have demonstrated that exposure to pro-inflammatory cytokines can modulate the phenotype and/or function of innate and adaptive immune cells ( 147 149 , 206 ), it is the work of Akbar et al that have specifically linked hyper-inflammation to impaired antigen specific immune responses during aging.…”
Section: Pathogen Eliminationmentioning
confidence: 99%
“…Whilst in vitro and in vivo studies have demonstrated that exposure to pro-inflammatory cytokines can modulate the phenotype and/or function of innate and adaptive immune cells ( 147 149 , 206 ), it is the work of Akbar et al that have specifically linked hyper-inflammation to impaired antigen specific immune responses during aging. Using a human experimental system that investigates antigen-specific immunity in vivo , the group has consistently demonstrated an age-related impairment in the delayed type hypersensitivity (DTH) response to varicella zoster virus (VSV) antigen ( 204 , 205 , 207 ). Attributed to aberrant activation of P38 MAPK signaling, the decreased VZV antigen responsiveness of older adults is associated with an accumulation of CCR2 + monocytes that inhibit T cell proliferation via the production of prostaglandin E2 (PGE 2 ) ( 204 , 205 ).…”
Section: Pathogen Eliminationmentioning
confidence: 99%
See 3 more Smart Citations